PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN KEJUJURAN PEMIMPIN TERHADAP EFISIENSI DI SEKOLAH MENENGAH PERTAMA NEGERI 21 BATANG HARI - Sukatin Sukatin; Zulqarnain Zulqarnain; Maya Nur Khasanah (HIKMAH: JURNAL PENDIDIKAN AGAMA ISLAM, 2022)
To create such conditions, transformational leadership and leadership honesty are needed. This study aims to determine and analyze: (1) The effect of transformational leadership on school efficiency. (2) The effect of leader honesty on school efficiency. (3) The influence of transformational leadership and honesty of leaders both have an effect on school efficiency. Research using quantitative methods, used to examine the population or a particular sample. The population in this study were all teachers at the 21 Batang Hari Junior High School, because the population was less than 100, the sample of this study were all 31 teachers at the 21 Batang Hari Junior High School. different, that is 1/3 of the total sample in SMP N 3 Batang Hari, which is 10 teachers. Collecting data using questionnaires and observations, the data has met the validity test, reliability test, normality test, homogeneity test and linearity test and hypothesis testing. Shows that: (1) The measurement of transformational leadership on efficiency is 47.9%. Calculation of tcount with ttable obtained tcount = 3.359, ttable = 1.695 that rejects Ho and accepts Hi. This means that there is a significant influence between transformational leadership and school efficiency. (2) The effect of leader honesty on school efficiency is 53.3%. Calculation of tcount with ttable obtained tcount = 3.793, ttable = 1.695 that rejects Ho and accepts Hi. There is a significant influence between the honesty of the leader on the efficiency of the school. (3) The simultaneous effect of transformational leadership and leadership honesty on school efficiency is 95.5%. The calculation of fcount with ftable obtained fcount = 295.697, ftable = 3.30 that rejects Ho and accepts Hi. There is a significant effect between transformational leadership and leadership honesty simultaneously on school efficiency